Geological risk management - Khan, Aftab Alam (Journal of Nepal Geological Society, 2004)
Geological risk management depends on the understanding of the underlying geological processes and their control on various geohazards. The significant responsibilities are post-crisis analysis with scenario formulation to develop strategies to mitigate the impact of future events and preparation of coordinated risk assessments for regions vulnerable to natural hazards. The evaluations are essential for developing hazard-resistant structures, building codes, better land use planning, hazard minimising policy, and emergency response plans. Two vital geological hazard scenarios, such as earthquake and arsenic contamination in groundwater in the Ganges-Brahmaputra-Meghna delta of Bangladesh, are elaborated as case studies. A complete cycle of seismic hazard assessment to seismic risk management is proposed. An earthquake prediction to risk management mechanism is identified together with the coordinated professional effort is for seismic risk assessment. The geological processes responsible for arsenic contamination in groundwater are pointed out and the role of geology in managing various geohazards is highlighted.